Meningkatkan Motivasi Belajar Matematika Siswa kelas XII IPA.1 SMA Negeri 3 Barru Melalui Pembelajaran dengan Pendekatan Problem Posing - Busran (Issues in Mathematics Education (IMED), 2019)
This research is classroom action research which aims to increase motivation to learn mathematics in students of Class XII IPA.1 Barru 3 Public High School through problem posing learning. The research subjects were students of class XII IPA.1 30 SMA 3 Barru Academic Year 2017/2018 amounted to 30 people consisting of 7 men and 23 women. The implementation of this study consisted of two cycles. Data collection techniques are observation, questionnaire and giving test of learning outcomes to each research subject. The research data is in the form of student learning motivation data and student learning outcomes data. The results showed that: (1) student activities in mathematics learning experienced an increase from the first cycle with an average of 65%, increased to 76.60% in the second cycle, there was an increase of 11.60% or from the sufficient category to be good, (2) student learning motivation has increased from cycle I to cycle II, for the level of attention there is an increase of 6.33%, for the level of relevance there is an increase of 14.42%, for the level of confidence there is an increase of 5.50%, and for the level of satisfaction there an increase of 2.56%, and (3) student learning outcomes in mathematics learning experienced an increase from cycle I, classical learning completeness from 14 students (46.67%) to 25 students (83.33%) in cycle II. The results of the study show that learning with a problem posing approach can increase student motivation so that teachers are expected to be able to apply the problem posing model as a variation in mathematics learning.